The role of electronic management in developing the work environment in public sector institutions in Asir region - Alyausi, Asma Ali; Alshaebi, Mohammed Alsagheer Qasem (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to identify the role of electronic management in developing the work environment in government sector institutions in Asir region.  The researcher used the descriptive and analytical approach to achieve the objectives of the study. She applied a questionnaire on a simple random sample of (350) employees from the government sector in Asir region. The study found results, the most important results are: The governmental sector institutions in Asir region apply electronic management to a large number of approvals, with an average of (4.18). The field of electronic regulation came at the forefront of the achieved fields, with an arithmetic average (4.23). It followed by the field of electronic control, with an average of (4.19). Then, the field of electronic planning, with an arithmetic average (4.15). Finally, the field of electronic guidance, with an arithmetic mean (4.14). The results also showed the existence of a positive correlation between electronic management and the reality of the work environment. It also revealed the existence of a statistically significant effect of electronic management in its various dimensions on developing the work environment in government sector institutions in Asir region. The results also revealed that there are no statistically significant differences at the significance level (a ≤ 0.05) between the averages of the study sample responses about the role of electronic management in developing the work environment in government sector institutions in Asir region, due to the difference of sex, age, educational level, job position, and the number of years of experience. While there were differences attributed to the difference in the employer in the axis of electronic administration, the differences were in favor of the General Department of Passports branch.
Keywords: Electronic management; Work environment; Government sectors; Asir region